ANALISIS MISKONSEPSI PADA MATERI PROGRAM LINEAR MENGGUNAKAN THREE-TIER TEST DI SMA NEGERI 1 PONTIANAK - Arif Dwi Rahmadhani; Edy Yusmin; Hamdani Hamdani (Universitas Tanjungpura, 2019)
AbstractThe purpose of this research was to analyze, describe and resolve student’s misconception in linear programming at SMAN 1 Pontianak. Three-tier Test can be used to identify student’s misconceptions. There were three categories of misconceptions that will be discussed in this study, namely systematic misconception, random misconception and misconception due to carelessness. This study used a descriptive-exploratory method with a qualitative approach. Data collection techniques were written tests and interviews, while data collection tools were Three-tier Test and unstructured interview. The research subjects were 32 of 11th grade science students at SMAN 1 Pontianak in 2019/2020. The results of the research that student’s misconceptions on linear programming were students wrong in understanding a concept of problems in linear programming, so students had difficulty in answering questions that related to the concept. Meanwhile, to resolve student’s misconceptions were by discovering the causes of misconceptions first, then looked for concepts that were still had misconceptions and fixed misconceptions by giving questions related to concepts and rebuilding student concepts.Keywords: Misconception, Linear Programming, Three-Tier Test